Analysis of web based learning use in a first course of algorithmics - Madoz, María Cristina (2005)
This paper presents an analysis of the aspects to take into account when reformulating the teaching and learning processes of a first course of Algorithmics employing elements of Distance Education in a Web-based virtual environment. Particularly it analyzes a large experience (more than 1000 students) carried out in the initial subject of Algorithmics (Computer Programming, annual subject), of the School of Computer Sciences at the UNLP, on three different student's profiles. In addition, this paper discusses the difficulties of distance education on subjects with an important experimental component, such as the analyzed first course of Algorithmics. Finally, the results obtained in the initial evaluation of the different student profiles are presented, analyzing the advantage and disadvantages of using these technologies in the initial graduate courses on Computer Sciences.